Portal Vein Thrombosis in Patients With Cirrhosis Undergoing Elective Transjugular Intrahepatic Portosystemic Shunt: Risk Factors, Warfarin Efficacy, and Clinical Outcomes. (April 2018) - Yue-Meng, Wan; Li, Yu-Hua; Wu, Hua-Mei; Yang, Jing; Yang, Li-Hong; Xu, Ying
Portal vein thrombosis (PVT) is a common complication in cirrhosis. The aim of this study was to determine risk factors for PVT, assess the efficacy of anticoagulant therapy, and evaluate the effects of PVT on patients with cirrhosis undergoing elective transjugular intrahepatic portosystemic shunt (TIPSS). A total of 101 patients with cirrhosis undergoing elective TIPSS were prospectively studied. After TIPSS, all patients received preventive therapy for PVT and were followed up at 3, 6, 12, and 24 months. Clinical outcomes were compared between patients who developed PVT after TIPSS and those who did not. Multivariate analysis showed that white blood cell count (relative risk [RR]: 0.377; 95% confidence interval [CI]: 0.132-0.579; P = .001), Child-Turcotte-Pugh score (RR: 1.547; 95% CI: 1.029-2.365; P = .032), and ascites (RR: 1.264; 95% CI: 1.019-1.742; P = .040) were independent predictors for PVT. Warfarin treatment within 12 months achieved significantly higher rates of complete recanalization than aspirin or clopidogrel in patients with PVT (54.5% vs 31.3%; P = .013), although adverse events were similar between the 2 groups ( P > .05). Patients without PVT had significantly lower 2-year cumulative rates of variceal rebleeding (15.9% vs 36.6%; P = .023), shunt dysfunction (27.0% vs 46.8%; P = .039), hepatic encephalopathy (24.1% vs 42.6%; P = .045), and hepatocellular carcinoma (11.4% vs 31.2%; P = .024) and markedly higher 2-year cumulative survival rates (89.8% vs 72.9%; P = .041) than those with PVT. The PVT is associated with poorer clinical outcomes in TIPSS-treated patients, and warfarin is both safe and more effective in recanalizing PVT than aspirin or clopidogrel.